An Analysis of Directive Speech Act Translation Techniques and Quality in It Ends with Us by Colleen Hoover - Indrawati, Yuni; Sofyan, Dedi (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
The translation of expressive speech acts plays a crucial role in maintaining the original meaning and emotional tone of a literary work. This study aims to identify the translation techniques used and assess the quality of expressive speech act translations in the Indonesian version of It Ends With Us, translated by Ursula G. Buditjahja. A descriptive qualitative method with a single-case study approach was employed, using Spradley’s ethnographic analysis, including domain, taxonomy, componential, and cultural theme analyses. Data were collected from 118 expressive speech acts and evaluated through questionnaires to measure accuracy, acceptability, and readability based on Nababan’s (2012) translation quality assessment model. The analysis revealed 19 categories of expressive speech acts: thanking (14.41%), protesting (12.71%), agreeing (11.02%), blaming (9.32%), mocking (7.63%), apologizing (7.63%), praising (6.78%), farewelling (5.93%), and others with lower frequencies. Most translations were acceptable and understandable, although some were found to be inaccurate or less precise due to language misapplication. The overall translation quality scored 2.94, indicating a good level of translation. Eleven translation techniques were identified, contributing to the preservation of the novel’s themes and character development. The expressive speech acts were effectively translated, though greater attention to linguistic precision could enhance translation quality.